THE IMPACT OF AGILE AND ADAPTIVE BANKING TECHNOLOGY TRENDS IN SUPPORTING DIGITAL TRANSFORMATION FOR FINANCIAL COMPANIES - Anita Kusuma Dewi; Ahadi Rerung, Agus Sunaryo (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
Digital transformation has become a necessity for financial companies to remain competitive in the modern era. Agile and adaptive banking technology trends play a crucial role in this process, enabling financial companies to respond to market changes more quickly and efficiently. Agile technologies, such as artificial intelligence, big data, and cloud computing, support process automation, reduce operational costs, and increase efficiency and speed of service. In addition, technological adaptation allows the development of more innovative products and services, in line with evolving customer needs. The application of advanced technologies also improves data and transaction security, reduces the risk of fraud, and ensures compliance with applicable regulations. The impact and implications of agile and adaptive banking technology trends in supporting digital transformation are broad and profound. Financial companies that successfully utilize these technologies will be able to increase efficiency, improve customer experience, reduce risk, and maintain their competitiveness in an increasingly digital and connected market. This study summarizes the positive impacts of implementing modern banking technologies in supporting digital transformation for financial companies, while also underlining the importance of innovation and adaptability in this dynamic industry.